IMPLEMENTATION OF EDUPRENEURSHIP THROUGH THE TEACHING FACTORY IN VOCATIONAL HIGH SCHOOL OF HOTEL ACCOMMODATION: CASE STUDY AT SMK N 6 YOGYAKARTA - Kuat, Tri (Journal of Vocational Education Studies, 2018)
The purpose of this study is to know, to describe, and to analyze the implementation of edupreneurship through teaching factory in the vocational high school (SMK) majoring in hotel accommodation program skill. The research method used in this research is the qualitative method. This method is intended to know deeply in the implementation of edupreneurship through teaching factory in SMK. This research started with the observation of edupreneurship activity through teaching factory at SMK N 6 Yogyakarta. The data was collected by conducting in-depth interviews with informants who are directly involved in edupreneurship activities. The result of this research is the implementation of edupreneurship through teaching factory in terms of learning, there is commitment and basic principle which run by the school but not yet optimal. There are still significant obstacles, especially related to the work culture that is applied not in accordance with the procedures of business and industry (DUDI), educators who have not understood the culture of DUDI, facilities, and infrastructure that do not meet the DUDI standards, the cooperation between SMK and DUDI is still weak, and the regulation of the Supreme Audit Agency (BPK) which requires the use of state-owned goods as a form of state income.